A documentary approach to gentrification due to tourism in rural spaces - Zarza Ballina, Joana (2024)
Tourism as a solution to the problems of rural communities has generated various unwanted situations such as gentrification, which has diverse environmental implications. The aim of the article is to analyze the scientific production on tourism-related gentrification to identify knowledge gaps and formulate research proposals that contribute to the topic. For this purpose, documents from 2008 to 2022 were consulted, including open access sources on Google Scholar and restricted access from Elsevier. This resulted in categorization into four thematic lines: Socio-spatiality and Socio-spatial and Sociocultural Impacts of Tourism-related Gentrification, Capitalism and Displacement, Gentrification in Rural Areas, and Gentrification and Government. It is concluded that the third line is of increasing interest in publications on gentrification, given the challenges faced by rural tourist areas.